2005
DOI: 10.1080/08820530500232126
|View full text |Cite
|
Sign up to set email alerts
|

Vogt-Koyanagi-Harada Disease

Abstract: Vogt-Koyanagi-Harada disease (VKH) is a multisystem autoimmune disorder principally affecting pigmented tissues in the ocular, auditory, integumentary and central nervous systems. Patients are typically 20 to 50 years old and have no history of either surgical or accidental ocular trauma. Pigmented races are more commonly affected. Depending on revised diagnostic criteria, the disease is classified as complete, incomplete or probable based on the presence of extraocular findings (neurological, auditory and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
1
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 31 publications
4
77
1
13
Order By: Relevance
“…The precise pathogenesis remains unidentified in the vast majority of patients, however. [1][2][3][4][5][6] While corticosteroids are the mainstay of therapy and are required to control active inflammation during episodes of acute or recurrent inflammation, cumulative evidence supports the first-line use of corticosteroid-sparing immunosuppressive agents to reduce the risk of recurrence, decrease the development of late complications, and improve long-term vision. [16][17][18][19][20] Multimodal imaging studies, particularly fluorescein angiography and spectral domain-ocular coherence tomography (SD-OCT), are important adjuncts for initial diagnosis and early monitoring of treatment response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The precise pathogenesis remains unidentified in the vast majority of patients, however. [1][2][3][4][5][6] While corticosteroids are the mainstay of therapy and are required to control active inflammation during episodes of acute or recurrent inflammation, cumulative evidence supports the first-line use of corticosteroid-sparing immunosuppressive agents to reduce the risk of recurrence, decrease the development of late complications, and improve long-term vision. [16][17][18][19][20] Multimodal imaging studies, particularly fluorescein angiography and spectral domain-ocular coherence tomography (SD-OCT), are important adjuncts for initial diagnosis and early monitoring of treatment response.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Four stages of VKH disease are recognized, including prodromal, acute uveitic, convalescent, and chronic/recurrent uveitic. A history of penetrating ocular trauma or surgery prior to the onset of uveitis precludes the diagnosis.…”
mentioning
confidence: 99%
“…The extraocular symptoms are predominantly neurologic/auditory manifestations: meningismus, tinnitus, and sensorineural hearing loss [10]. Ondrey et al [11] reported that 33.3% of patients with VKH disease had sensorineural hearing loss in the acute phase despite the small sample size and that patients with untreated VKH disease might have more severe hearing abnormalities than that observed in their study, because all had already been treated for severe ocular inflammation.…”
Section: Ishibazawa Et Almentioning
confidence: 73%
“…Todas as entidades clínicas causadoras de efusão cílio-coroidiana secundária formam o diagnóstico diferencial da sín-drome de efusão uveal idiopática, são elas: síndrome de VogtKoyanagi-Harada (2) ; nanoftalmia (5,7) , tumores coroidianos (metástases, linfoma, melanoma) (1,4) ; mixedema (5) ; esclerite (1) ; sífi-lis (6) ; toxoplasmose (1) ; coroidorretinopatia serosa central idiopática (12) ; fístula carótido-cavernosa (1) ; oftalmia simpática (1) e pseudotumor orbitário (1) . O presente estudo relata um caso de efusão uveal secundária, sendo a tuberculose ocular a etiologia mais provável, diagnosti- apresentações clínicas, nenhum caso evoluiu com efusão uveal (16) .…”
Section: Discussionunclassified
“…Classifica-se a efusão cílio-coroidiana ou efusão uveal como uma reação não específica observada em várias entidades clínicas (1) , podendo estar associada às doenças sistê-micas como Vogt-Koyanagi-Harada (1)(2) ; apresentar causas específicas como cirurgias oculares (3) ou pós-traumáticas (1) ; quadros não inflamatórios como leucemias (1) , mieloma múltiplo (1) , tumor de glândula lacrimal (1) , linfomas (4) , alterações vasculares (fístula carótido-cavernosa) (1) ou surgir após fotocoagulação retiniana (1) . O mixedema também é descrito como causa de efusão uveal (5) .…”
Section: Introductionunclassified